2005
DOI: 10.2514/1.9460
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Flow Around Square Cylinders at Incidence by Using a Rod

Abstract: Aerodynamic characteristics of a square cylinder at incidence were investigated experimentally in the wake of a small rod at a Reynolds number of 3.4 × × 10 4 . The dimensionless gap L/D was varied from 1.71 to 8.00. Depending on the spacing L/D, two flow patterns with and without vortex shedding from the rod were observed. Pressure measurements on the rod and square cylinder and hot-film measurements in the wake of the cylinder were carried out. The combined influences of the rod and angle of incidence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Other investigators, e.g. , Dutta et al (2003), and Sarioglu et al (2005), reported similar trends for the behavior of the aerodynamic forces and vortex shedding.…”
Section: Introductionsupporting
confidence: 54%
“…Other investigators, e.g. , Dutta et al (2003), and Sarioglu et al (2005), reported similar trends for the behavior of the aerodynamic forces and vortex shedding.…”
Section: Introductionsupporting
confidence: 54%
“…Flow control around the cylinder with the help of control rod [1][2][3][4], splitter plate [5][6][7] can be given as literature examples. Especially, flow around a circular cylinder has encountered in many engineering applications, for example, in the cooling tower, chimney and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, flow around a circular cylinder has encountered in many engineering applications, for example, in the cooling tower, chimney and so forth. Sarioglu et al [3] and Igarashi [8] investigated experimentally the effects of a thin rod having circular cross section, placed before a square cylinder in different distances, on the flow. They showed that there are two different flow structures depending upon the gap ratio between the two objects.…”
Section: Introductionmentioning
confidence: 99%
“…If a circular rod is positioned upstream of the square one a second non-shedding mode is possible [54] depending on the distance between the rods. Smoke visualisation of the shedding and not-shedding modes is shown in figures 2.5a and 2.5b.…”
Section: Instantaneous Flow Visualisationsmentioning
confidence: 99%
“…(a) Vortex shedding [26], Re D = 11000 (b) Non-shedding controlled by an upstream circular rod [54], Re D = 34000 Figure 2.5: Smoke visualisation of the wake of a square rod from Igarashi [26] and Sarioglu [54].…”
Section: Pressure On the Rod Surface At Different Angles Of Attackmentioning
confidence: 99%